Dietro al microfono. Intellettuali italiani alla Radio svizzera (1930-1980) - Valsangiacomo, Nelly (Itinerari, 2015)
A gripping essay on the role that Italian intellectuals played in the organization and scheduling of Swiss public radio between the Fascist period and the so-called Anni di Piombo (Years of Lead). The book What was the role of Italian intellectuals in the history of Swiss radio broadcasting culture? And what images of Switzerland and Italy were conveyed between 1930 and 1980? Ever since it began in the 1930s, Italian-language Swiss radio, a national public service broadcaster addressed to a linguistic minority, drew from intellectual resources external to its own political borders, a characteristic that contributed to defining its profile. During the Fascist period, for example, Italian intellectuals could express themselves from the microphones of this radio with a freedom that they were not allowed in their home country: Benedetto Croce's 1936 speech is a memorable case in point. Subse-quently, when the interview and debate formats tended to undermine that of the radio lecture, journalists and writers such as Pier Paolo Pasolini and Eugenio Montale took advantage of the debating space that Swiss Italy offered them. By analysing the written and audio sources, many of which unpublished, Nelly Valsangiacomo's essay reconstructs a complex as well as fascinating radio broadcasting panorama, brought to life by the voices of some of the greatest Italian intellectuals, such as Elio Vittorini, Maria Corti, Indro Montanelli, and Dario Fo. Voices that can now be listened to once again thanks to a web page completing the book: www.rsi.ch/dietroalmicrofono (Radiotelevisione svizzera di lingua italiana/Italian-language Swiss Radio and Television)